High-Performance Sensing Behavior Using Electronic Ink of 2D SnSe2 Nanosheets. - Pawar, Mahendra; Kadam, Sunil; Late, Dattatray J. (Chemistry Select, 2017)
Most of the recent research work on layered chalcogenides is understandably focused on single atomic layers. However, it is uncertain if the single layer units are most ideal structures for enhanced gas-solid interactions. To probe this concern, we have synthesized few layer thick SnSe<span style="line-height: 0; bottom: -0.25em; margin: 0px; padding: 0px 1px; border: 0px; outline: 0px; font-size: 0.688em; vertical-align: baseline; background: 0px 0px rgb(249, 249, 249); position: relative; color: rgb(51, 51, 51); font-family: "Open Sans", Arial, Helvetica, "Lucida Sans Unicode", sans-serif;">2 nanosheets ink using liquid exfoliation method. The morphology, thickness / layering and elemental analysis of the sheets were characterized by using SEM, TEM, AFM, Raman spectroscopy and by XPS. The two dimensional (2D) SnSe<span style="line-height: 0; bottom: -0.25em; margin: 0px; padding: 0px 1px; border: 0px; outline: 0px; font-size: 0.688em; vertical-align: baseline; background: 0px 0px rgb(249, 249, 249); position: relative; color: rgb(51, 51, 51); font-family: "Open Sans", Arial, Helvetica, "Lucida Sans Unicode", sans-serif;">2 nanosheets sensor device with different thicknesses was assessed for the humidity and gas sensing performances with exposure to humidity in different conditions. The results show that compared to the bulk / thicker counterpart, sensor device of few SnSe<span style="line-height: 0; bottom: -0.25em; margin: 0px; padding: 0px 1px; border: 0px; outline: 0px; font-size: 0.688em; vertical-align: baseline; background: 0px 0px rgb(249, 249, 249); position: relative; color: rgb(51, 51, 51); font-family: "Open Sans", Arial, Helvetica, "Lucida Sans Unicode", sans-serif;">2 layers exhibit excellent sensitivity, recovery and ability to be tune the sensing performance with thickness and can be used in lab on chip devices.